To determine which expressions are equivalent, we will simplify each expression step by step.
-
Expression: \((-3.9b + a) + (-1.7b + 4.9a)\)
Simplification: \[ = -3.9b - 1.7b + a + 4.9a = (-3.9 - 1.7)b + (1 + 4.9)a = -5.6b + 5.9a \]
-
Expression: \((3.4a - 1.7b) + (2.5a - 3.9b)\)
Simplification: \[ = 3.4a + 2.5a - 1.7b - 3.9b = (3.4 + 2.5)a + (-1.7 - 3.9)b = 5.9a - 5.6b \]
-
Expression: \(-0.4b + (6b - 5.9a)\)
Simplification: \[ = -0.4b + 6b - 5.9a = (-0.4 + 6)b - 5.9a = 5.6b - 5.9a \]
-
Expression: \(5.9a - 5.6b\)
This expression is already in simplest form.
-
Expression: \((2.5a + 1.6b) + (3.4a + 4b)\)
Simplification: \[ = 2.5a + 3.4a + 1.6b + 4b = (2.5 + 3.4)a + (1.6 + 4)b = 5.9a + 5.6b \]
Now, we can compare the results of the simplifications:
- Expression 1: \(-5.6b + 5.9a\) (which is equivalent to \(5.9a - 5.6b\))
- Expression 2: \(5.9a - 5.6b\)
- Expression 3: \(5.6b - 5.9a\) (this is not equivalent)
- Expression 4: \(5.9a - 5.6b\)
- Expression 5: \(5.9a + 5.6b\) (this is not equivalent)
From the simplifications, the equivalent expressions are:
- \((-3.9b + a) + (-1.7b + 4.9a)\)
- \((3.4a - 1.7b) + (2.5a - 3.9b)\)
- \(5.9a - 5.6b\)
Thus, the expressions that are equivalent are:
- \((-3.9b + a) + (-1.7b + 4.9a)\)
- \((3.4a - 1.7b) + (2.5a - 3.9b)\)
- \(5.9a - 5.6b\)
These can be summarized as options 1, 2, and 4 from the original list.